Implementasi RCM pada mesin diesel Deutz 20 kVA - Sunaryo, Sunaryo; Japri, Japri; Yuhelson, Yuhelson; Hakim, Legisnal (Universitas Muhammadiyah Metro, 2021)
The aspect that most influences the functioning of this telecommunications service is the aspect of maintaining the equipment or assets supporting the telecommunications service. For this reason, companies must periodically measure the performance of their maintenance so that telecommunications services continue to function properly. From the data, the frequency of damage to the diesel generator engine from 2017 to 2020 is very high. In the period 2017 to 2020 there were a total of 90 times the damage, and the biggest contributor to the damage was in the 20kVA Deutz diesel engine. The purpose of this research is to know how the maintenance conditions are and to know the level of effectiveness and to know the right recommendations to increase the effectiveness of the diesel generator engine. The research method used is RCM (Reliability Centered maintanance) which is a technique used to develop scheduled preventive maintenance. Research results obtained, the component whose frequency is often damaged in the Deutz generator diesel engine is the Alternator. This selection is based on the highest number of damage frequencies and the longest downtime for approximately 3 years. Calculation of the Alternator's Mean Time to Failure (MTTF) value is 25305 hours, which means that the Alternator component will experience damage again after operating for 25305 hours. While the Mean Time to Repair (MTTR) value of the Alternator is 22.54 hours, which means that the average time to repair the Alternator component is 22.54 hours. From the calculation of the Reliability Value, the alternator is said to still have a good function because the average value interval is still in the range 0 <R (t) <1. From the analysis results obtained the value of β of 1.64205. With this value (β> 1), the appropriate types of maintenance for the Alternator component are Preventive and Time Based Maintenance.Keywords: Reliability Centered Maintenance, Critical Components, Maintenance.